Building the evidence base on the agricultural nutrition nexus: Marshall Islands - Nelles, Wayne (Technical Centre for Agricultural and Rural Cooperation, 2018)
This report summarises results of a rapid country scan on the agriculture-nutrition nexus in the Republic of the Marshall Islands (RMI). Research included a desk review of accessible policies, programmes and other documents, published and unpublished, as well as a field mission to RMI from 11 to 30 December 2017. The mission allowed additional quantitative and qualitative data gathering with interviews, site visits and a small seminar to debrief interviews, present preliminary findings and discuss potential follow-up with some stakeholders.